The Effect Of Self-Efficacy On Self Actualization In Early Adulthood - Ayunanda, Sasha Nabila (Jurnal Psikologi, 2024)
Self-actualization is the highest level of human achievement; with it, people can fully explore themselves. To reach self-actualization, self-efficacy is required; having confidence in one's own talents is especially important in early adulthood. The most significant success in early adulthood is the ability to anticipate future needs for themselves. The goal of this research was to examine how self-efficacy affects self-actualization in early adulthood. Quantitative techniques are used in this research. A total of 172 people between the ages of 21 and 45 participated in this research. The sampling technique used is accidental sampling. A simple regression analysis technique was used for hypothesis testing. The results revealed a very significant effect with a value of 0.000 (p≤0.01) and an r-square value of 0.532, implying that self-efficacy affects self-actualization by 53.2%, with the remaining 46.8% influenced by another variable outside this research.